Beckett and media - Rapcsak, Balazs; Nixon, Mark; Schweighauser, Philipp (Manchester University Press, 2022)
Featuring twelve original essays by leading Beckett scholars and media theorists, this book provides the first sustained examination of the relationship between Beckett and media technologies. The chapters analyse the rich variety of technical objects, semiotic arrangements, communication processes and forms of data processing that Beckett's work so uniquely engages with, as well as those that - in historically changing configurations - determine the continuing performance, the audience reception, and the scholarly study of this work. Greatly enlarging the scope of earlier discussions, the book draws on a variety of innovative theoretical approaches, such as media archaeology, in order to discuss Beckett's intermedial oeuvre. As such it engages with Beckett as a media artist and examine the way his engagement with media technologies continues to speak to our cultural situation.